If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7w = 0 Reorder the terms: -7w + 6x = 0 Solving -7w + 6x = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6x' to each side of the equation. -7w + 6x + -6x = 0 + -6x Combine like terms: 6x + -6x = 0 -7w + 0 = 0 + -6x -7w = 0 + -6x Remove the zero: -7w = -6x Divide each side by '-7'. w = 0.8571428571x Simplifying w = 0.8571428571x
| 2q+8q-4=6 | | x^2+18x-448=0 | | 4x^2-19x+18=-4x+4 | | r^3=36 | | 6x^2-13x-63=0 | | 7x-2+3x=4+2x-2 | | -x=-(-10) | | 2x-7=3x+7 | | x^2+2x-1=4x+2 | | y=10x-18 | | 4x-7=-9+7x | | 4(c-3)=4c+8 | | -18-6x=10-10x | | 0.40*x+23=95 | | -20-3x=10-8x | | 2t+5=-3 | | x(3x-4)=152 | | 5x+9=86-6x | | 128=200.96x | | 3x-4=11x-28 | | 4x+22=11x-55 | | 2x-7x=34+23 | | 3x+2(x+2)=13-(2x+2) | | 6x+4x=15+5 | | 6(c-4)c=7 | | -2(-4n+3)+7n=12-(n+2) | | 48+16=32y | | 3x^2+13x-38=0 | | 6.142857143+-0.1428571429y=4.5+1.5y | | 7x+y=43 | | 18=9t-3t | | 2x-3y=9 |